In situ Creation of the Natural Phenolic Aromas of Beer: A Pulsed Electric Field Applied to Wort-Enriched Flax Seeds - Tsapou, Evangelia A.; Ntourtoglou, George; Drosou, Fotini; Tataridis, Panagiotis; Dourtoglou, Thalia; Lalas, Stavros; Dourtoglou, Vassilis (Frontiers in Bioengineering and Biotechnology, 2020)
To fine tune the production of phenolic aromas in beer, a pulsed electric field (PEF) is applied to beer wort, which is enriched with flax seeds. Fermentation is carried out with Saccharomyces and non-Saccharomyces yeast strains. Moreover, 4-vinylguaiacol (4-VG), a flavor highly active from volatile phenol, is produced by decarboxylation of ferulic acid (FA), or its inactive flavor and precursor (4-hydroxy-3-methoxycinnamic acid). All yeast strains can metabolize FA into 4-VG, using the pure compound in the synthetic medium or in flax seeds, with the best quantity produced by Saccharomyces cerevisiae as a precursor. PEF is applied to ground flax seeds, with and without beta glycosidase. The choice of flax seeds as a source of FA is based on its high content of ferulic precursors and their intrinsic nutritional value.